Management of neuromuscular diseases and spinal muscular atrophy in Latin America - Monges, Maria Rita (2017)
Latin America (LA) has a population of ∼645 million people distributed over 33 countries with marked political, cultural and economic differences. In LA, patients with inherited neuromuscular diseases (NMDs) often do not have access to specialized medical centers and many of them go undiagnosed. General management and care of spinal muscular dystrophy (SMA) patients in the region varies due to heterogeneous health care. An active generation of young clinical neurologists is being trained for the specialized care of SMA and other neuromuscular (NM) patients, both in the private and public sectors. The Euro-Latin-American Summer School of Myology (EVELAM) as well as efforts of professionals at large public centers in the major cities of LA have a leading role in this development. Different regional academic-scientific organizations as well as the expanding number of telethon centers and the creation of parent organizations, mostly concerning SMA, all together are contributing to the increased quality of the management of NMD patients. Over the past years, academic and clinical research, as well as the establishment of qualified centers for the molecular testing of NMD are pushing forward the creation of patient registries and the development of specific clinical trials, with Argentina and Brazil having a major role in this field. Nevertheless, increased awareness and further training of specialized health professionals are necessary to reach patients that are currently lacking care throughout the region.